EXPLORING CHALLENGES AND STRATEGIES IN TEACHING ENGLISH AS A SECOND LANGUAGE TO YOUNG LEARNERS - Aslan; Rasmita (Adisam Publisher, 2025)
Teaching English as a second language (ESL) to young learners presents a unique set of challenges and requires the use of effective and innovative strategies. Short attention spans, differences in learning pace and style, and the need to make learning relevant and engaging for children, are some of the key barriers faced by educators. Through this study, we explore various methods and approaches to overcome these challenges, including the use of props, games and other interactive activities that support visual, auditory and kinesthetic learning styles. The study also highlights the importance of differentiating teaching and adapting to each child's specific needs to maximise learning effectiveness. In addition, the establishment of a positive and supportive classroom environment, as well as classroom behaviour management, were seen as important factors in facilitating successful language learning. The conclusion of this study provides insights into effective strategies in educating young learners in ESL, demonstrating the importance of teaching approaches that are creative, flexible and responsive to individual needs.